Storytelling in Elementary Education: A Systematic Literature Review on Literacy Development - Iin Indrayanti; Rudi Hartono; Yuliati (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This study presents a systematic literature review on the role of storytelling in elementary education, with a particular focus on its impact on literacy development and vocabulary acquisition in Indonesian EFL context. Drawing on 75 articles published in Scopus, Eric and Sinta database from 2020 to 2025 between synthesized findings across diverse methodologies, and mixed method design. Results consistently enhance vocabulary mastery, learner engagement, and early literacy skills by providing contextualized language input, repeated word exposure, and opportunities for meaningful communication. Storytelling activities were also found to foster motivation, cultural identity, and multimodal literacy awareness, making them developmentally appropriate and pedagogically effective for young learners. The review concludes that storytelling is not merely a complementary classroom activity but a powerful instructional strategy that supports holistic literacy development and strengthens vocabulary acquisition in Indonesian elementary education.